Menumbuhkan Kecintaan Bahasa Inggris: Implementasi Metode English Fun di SD Negeri 020 Babulu - Ramdan, Muhamad; Febianti, Stela (Jurnal Pengabdian UntukMu NegeRI, 2024)
The English subject is often considered a challenging and tedious pressure for some students. Many of them face difficulties in learning a foreign language that is not their first language. As a result, interest in learning English tends to be low. However, to address this issue, a program called English Fun has been designed. The main objective of this program is to change the traditional perception of learning English by introducing fun and engaging methods. The implementation of this activity will take place on February 21, 2024, at SDN 020 Penajam Paser Utara, Desa Labangka Barat, Babulu District, Penajam Paser Utara Regency. This activity is conducted for 3rd grade students, totaling 36 children. Through this approach, students will be involved in various games, interactive activities, and using technology as a learning aid. Thus, English Fun not only increases students' motivation to learn English but also creates a more enjoyable and engaging learning environment.